Employee mobility & human capital in higher education level the moderating role of the opportunity cost of the employee on employees' mobility intentions - Hoyos Vallejo, Carlos Arturo (2016)
This study proposes for organizations with intensive use of knowledge, a model that predicts the employees´ mobility intentions, which includes not only the perceptions that employees have of extrinsic and intrinsic rewards received, and perceived organizational support to human capital, but also introduces the opportunity cost of the employee, as moderator of the relationship between rewards and intention to leave the organization. The data used was collected from different public and private universities in Colombia. The global model allows to proof of the existence of negative correlations between the exogenous constructs and the endogenous construct, as well as knowing the opportunity cost moderation in relations between the rewards described and intention to leave the organization. Findings suggest that in organizations with intensive use of knowledge, the perceptions that knowledge employees have, are an important predictor of intention to withdraw, therefore these perceptions could be an important input for managers, so as to devise policies and plans that include and facilitate high performance and satisfaction for high performance